Inventions - Robinson, W. Heath (William Heath), 1872-1944 (London Duckworth, 1999)
This is a collection of the comic fantasies of William Heath Robinson (1872-1944), whose name passed into the English language during his lifetime. The book covers the whole field of his comic work in peace and war, and an introduction tells the story of his life
Include Illustration
Keywords: English wit and humor, Pictorial -- Inventions